Frequency and susceptibility pattern of uropathogenic Enterobacteriaceae isolated from patients in Algiers, Algeria - Aouf, Abdelhakim; Gueddi, Taha; Djeghout, Bilal; Ammari, Houria (The Journal of Infection in Developing Countries, 2018)
Introduction: The frequency of Enterobacteriaceae involved in urinary tract infections (UTI) has increased significantly since the early 1990s, particularly in at-risk facilities such as resuscitation, surgery, urology and nephrology. The objective of this study was to evaluate the antimicrobial susceptibility of Enterobacteriaceae causing urinary tract infections (UTIs)at the University Hospital Centre of Benimessous in Algiers. Methodology: The study was designed as a retrospective study (between January 1st 2010 and December 31st 2012) and a prospective study (between January 1standApril 30th 2013) on 13,611 urine samples. Antimicrobial resistance phenotyping was conducted on the bacterial isolates using disk-diffusion method. Results: On 13,611 urine samples analysed, 1,790 (13.15%) fulfilled the criteria for urinary tract infection. Enterobacteriaceae were identified in 1,561 analysed samples (87%). Escherichia coli was the dominant uropathogen (66,15%) in both hospitalized and non-hospitalized patients. The other main detected Enterobacteriaceae members were Klebsiella pneumoniae (11,96%) and Proteus mirabilis (5,42%). Analysis of results showed also that women were more prone to UTI than men with sex ratio of 3.76(W/M). The susceptibilities of isolated Enterobacteriaceae to antibiotics revealed that they had acquired resistance to several classes, particularly toward β-lactams. Resistance frequencies were relatively high to ampicillin and sulfomethoxasole, while being very low to aminoglycosides and furans. Results obtained revealed also that 7% of isolates where resistant to third generation cephalosporins by production of extended spectrum β-lactamases (ESBL). Conclusions: The continuous monitoring of antibiotic resistance of uropathogenic Escherichia coli is crucial to guide the clinician to choose the best empiric treatment.